2019
DOI: 10.1071/am18026
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring suggests bat boxes may alter local bat community structure

Abstract: Bat boxes are often used to provide supplementary roosting habitats; however, little is known of their impacts on community composition. Data collected from a 25-year box-monitoring and 31-year harp trapping case study provides preliminary evidence that the installation of boxes may have contributed to one species, Gould’s wattled bat (Chalinolobus gouldii), dominating the bat community of a periurban park in Melbourne. This highlights the need for systematic monitoring and empirical assessment of conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The relative activity of each species or complex differed between the sites, with no clear or consistent patterns corresponding to the different treatments and survey periods. This suggests that, while use of bat boxes by widespread, adaptable species (such as C. gouldii) may have some influence on localised patterns of community composition 26 , it does not necessarily result in a consistent, widespread dominance of generalist species, or a reduction in overall bat diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The relative activity of each species or complex differed between the sites, with no clear or consistent patterns corresponding to the different treatments and survey periods. This suggests that, while use of bat boxes by widespread, adaptable species (such as C. gouldii) may have some influence on localised patterns of community composition 26 , it does not necessarily result in a consistent, widespread dominance of generalist species, or a reduction in overall bat diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence documented two occasions where C. gouldii roosted together with N. geoffroyi in a box (unpublished data), which suggests that if C. gouldii is behaviorally dominant, it may be seasonally dependent or differ between sexes. More research is required to better understand the commonly reported box dominance by C. gouldii and its potential consequence for other species (Rueegger ; Griffiths et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence suggests that few bat species readily take up boxes, although this may in part be due to a paucity of studies (Goldingay & Stevens ; Rueegger ). There is also concern that bat boxes may lead to some species becoming locally dominant (Rueegger ; Griffiths et al ). Microclimate within bat boxes may be an important cue for selection by bats (Goldingay & Stevens ); however, studies specifically testing for this are scarce in Australia (but see Doty et al ).…”
Section: Introductionmentioning
confidence: 99%
“…We collected all bats roosting in the boxes, identified them to species, and recorded a range of morphometric data for each individual. The bat boxes at the study site are predominantly occupied by the Gould's wattled bat (Chalinolobus gouldii; Griffiths et al 2017Griffiths et al , 2019Griffiths et al , 2020, which was the focus of this study. The Gould's wattled bat is a small, widespread and generalist insectivorous bat species, with an average body mass of 14 g and forearm length of 44 mm (Churchill 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Native fauna includes 11 tree-roosting bat species (Griffiths et al 2020). Forty bat boxes were installed within the riparian zone of Jacksons Creek at OPNP, commencing in 1992 (Irvine and Bender 1995), and have since been monitored regularly as part of a larger ongoing study (Griffiths et al 2019(Griffiths et al , 2020Godinho et al 2015Godinho et al , 2020. The bat boxes were constructed from timber and based on the Stebbings and Walsh (1985) rectangular cuboid design (Godinho et al 2020).…”
Section: Study Areamentioning
confidence: 99%